Hubungan Pengetahuan Ibu Tentang Imunisasi Dasar dengan Kelengkapan Imunisasi Dasar Bayi di Wilayah Kerja Puskesmas Pacar Keling Surabaya - Maufiroh Risfin Andini (SENTRI: Jurnal Riset Ilmiah, 2026)
The aim of this research is to discuss the level of knowledge of mothers in Surabaya regarding complete basic immunization, and whether their knowledge is a factor that influences the completeness of basic immunization for babies. This research is a descriptive qualitative study, with data obtained through interviews with 2 mothers with babies and 1 health worker, namely a midwife. Data were analyzed using the Miles and Huberman model. The results of the research show that the majority of babies in the Pacar Keling Community Health Center area have received complete basic immunization because mothers have good knowledge regarding immunization. This shows that maternal knowledge is a factor in fulfilling complete basic immunization for babies. However, immunization outreach has not been carried out as comprehensively as in seminars, only through Posyandu and Community Health Centers, so that mothers are reduced to only attending health facilities. There is a need for outreach in the form of seminars so that immunization education can be provided comprehensively to mothers in the Pacar Keling Community Health Center area with the hope of increasing the target of complete basic immunization for babies.